2023
DOI: 10.3390/d15060713
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Old Relicts in Structuring the Boreal/Tropical Transitional Zone: The Case of East Asian Planktonic Cladocera (Crustacea)

Ivan I. Krolenko,
Petr G. Garibian,
Alexey A. Kotov

Abstract: Previous studies provided evidence of the mixing of boreal–tropical cladocerans (Crustacea) in the Far East of Eurasia, as well as the presence of numerous pre-Pleistocene relict endemics. In this study, we hypothesize that the colonization history is reflected in the proportions of endemic/boreal/tropical taxa among different habitat types within this region. We analyzed 442 qualitative samples collected from seven sub-regions of the Far East of Russia and South Korea along a latitudinal transect of approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
2
0
0
Order By: Relevance
“…Most probably, after our records, just Ciscaucasia must be regarded as its northernmost distribution region (up to 43°N). Therefore, we have demonstrated that Ciscaucasia is a region of penetration of the tropical fauna to European Russia similarly to the earlier studied Primorie in the Far East of Russia (Kotov, 2016;Chertoprud et al, 2023;Krolenko et al, 2023).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Most probably, after our records, just Ciscaucasia must be regarded as its northernmost distribution region (up to 43°N). Therefore, we have demonstrated that Ciscaucasia is a region of penetration of the tropical fauna to European Russia similarly to the earlier studied Primorie in the Far East of Russia (Kotov, 2016;Chertoprud et al, 2023;Krolenko et al, 2023).…”
Section: Discussionsupporting
confidence: 83%
“…This thermophylic and eurybiotic species lives in the coastal zone of lakes, slow flowing rivers, temporary water bodies and rice paddies (Korovchinskyi et al, 2021). We can confirm that O. cambouei belongs to the "southern tropical" faunistic complex, according to Kotov (2016), see also Krolenko et al (2023) andChertoprud et al (2023) for a further development of these ideas. Previously, the species was found in Africa, including Madagascar, the Iberian Peninsula, subtropical and tropical regions of Asia; vicinities of the city of Aksakan (Northwest Kazakhstan, 48°N) were regarded as its most northern distribution point (Sinev, 2015;Korovchinskyi et al, 2021).…”
Section: Discussionsupporting
confidence: 65%